Endometriosis education in schools: A New Zealand model examining the impact of an education program in schools on early recognition of symptoms suggesting endometriosis. (28th March 2017) - Bush, Deborah; Brick, Emily; East, Michael C; Johnson, Neil
Abstract : Background: Menstrual morbidity plays a significant role in adolescent females' lives. There are no studies to date reporting such data from menstrual health education programs in schools. Aims: The aim of our study was to report results from an audit of a menstrual health and endometriosis education program in secondary schools and observe age patterns of young women presenting for menstrual morbidity care. Materials and methods: Audit data from education in secondary schools and audit data of patients from an Endometriosis and Pelvic Pain Coaching clinic operating in a private endometriosis specialised centre are reported. Results: In a region of consistent delivery of the education program, student awareness of endometriosis was 32% in 2015. Overall in 2015, 13% of students experienced distressing menstrual symptoms and 27% of students sometimes or always missed school due to menstrual symptoms. Further, in one region of consistent delivery of the menstrual health education program, data show an increase in younger patients attending for specialised endometriosis care. Conclusions: There is strong suggestive evidence that consistent delivery of a menstrual health education program in schools increases adolescent student awareness of endometriosis. In addition, there is suggestive evidence that in a geographical area of consistent delivery of the program, a shift in earlier presentation of young women to a specialised health service is observed.